2018
DOI: 10.1177/1464884918797611
|View full text |Cite
|
Sign up to set email alerts
|

Peace journalism on a shoestring? Conflict reporting in Nigeria’s national news media

Abstract: Conflicts that occur across ethnic and/or religious identity lines generally have underlying root causes such as economic marginalization and political competition. Yet when these causes are ignored by politicians and the media, and conversely differences in ethnicity and religion are simply propagated as the main conflict causes, this may have serious consequences for people’s perceptions concerning the possibility and feasibility of peaceful conflict resolution and coexistence. In this paper, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Interviewees were unanimous that ethnoreligious considerations impact significantly on the willingness of journalists to carry out investigative reporting. This is consistent with past research, which has identified primordial sentiments as a major challenge to newspaper coverage especially contentious issues (Demarest & Langer, 2018;Uche, 1989;Yusha'u, 2015). The media in Nigeria developed and crystallized along ethnic lines especially during the period leading to independence and the First Republic (Adebayo, 2017).…”
Section: Ethno-religious Considerationssupporting
confidence: 92%
See 1 more Smart Citation
“…Interviewees were unanimous that ethnoreligious considerations impact significantly on the willingness of journalists to carry out investigative reporting. This is consistent with past research, which has identified primordial sentiments as a major challenge to newspaper coverage especially contentious issues (Demarest & Langer, 2018;Uche, 1989;Yusha'u, 2015). The media in Nigeria developed and crystallized along ethnic lines especially during the period leading to independence and the First Republic (Adebayo, 2017).…”
Section: Ethno-religious Considerationssupporting
confidence: 92%
“…Nigeria is adjudged to have one of the most robust and freest media in Africa (Demarest & Langer, 2018). The 1999 Nigerian Constitution in Chapter 11, Section 22, guarantees freedom of the press.…”
mentioning
confidence: 99%
“…Propaganda, partiality, and partisanship were all charges levelled against war journalists. Journalists and media outlets who follow a peace journalism model discuss where the conflict comes from in their news reports (Demarest & Langer, 2021). They also stress the experiences of normal citizens, moving beyond the viewpoints of the two "warring" factions.…”
Section: Journalism For Peace and Conflict Resolutionmentioning
confidence: 99%
“…For instance, responding to the critique of foreign coverage, most journalists interviewed by Rodny-Gumede (2016) recognized the need to prioritise peace narratives, and to include a wider range of sources and alternative views, even if PJ was unfamiliar. While the reporting of Africa by international media is often researched, the role of local journalists is not (Bunce, 2010) albeit a few scholars are active therein (see, inter alia, Hyde-Clarke, 2011;Youngblood, 2017b;Adebayo, 2017Adebayo, , 2018Demarest andLanger, 2018, Ogenga, 2019). Broadly speaking, these studies conclude that notwithstanding advantages and limitations, certain aspects of PJ are worth implementing when reporting African conflicts and other sensitive issues.…”
Section: Peace Journalismmentioning
confidence: 99%